2022
DOI: 10.3389/fpls.2022.905181
|View full text |Cite
|
Sign up to set email alerts
|

GhHAI2, GhAHG3, and GhABI2 Negatively Regulate Osmotic Stress Tolerance via ABA-Dependent Pathway in Cotton (Gossypium hirsutum L.)

Abstract: The type 2C protein phosphatases (PP2Cs) are well known for their vital roles in plant drought stress responses, but their molecular mechanisms in cotton (Gossypium hirsutum L.) remain largely unknown. Here, we investigated the role of three clade A PP2C genes, namely, GhHAI2, GhAHG3, and GhABI2, in regulating the osmotic stress tolerance in cotton. The transcript levels of GhHAI2, GhAHG3, and GhABI2 were rapidly induced by exogenous abscisic acid (ABA) and polyethylene glycol (PEG) treatment. Silencing of GhH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…7 b). These target genes include several stress-responsive genes such as PP2C [ 30 ], GST8 [ 31 ], PR , and HSP20 [ 32 ]; protein kinases and phosphatase genes involved in stress response such as CIPK6 [ 33 ], PFK4 [ 34 ], and HAI2 [ 10 ]; transport-related genes such as PDR , NRT2.4 [ 35 ], and ANN5 [ 36 ]; and 17 TF encoding genes such as TGA4 [ 37 ], WRKY23 [ 38 ], and HB-7 [ 25 ] (Additional file 2 : Table S8). Overall, we identified a series of genes both related to 3D chromatin structure and induced by drought stress, which are closely related to cotton response to drought stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 b). These target genes include several stress-responsive genes such as PP2C [ 30 ], GST8 [ 31 ], PR , and HSP20 [ 32 ]; protein kinases and phosphatase genes involved in stress response such as CIPK6 [ 33 ], PFK4 [ 34 ], and HAI2 [ 10 ]; transport-related genes such as PDR , NRT2.4 [ 35 ], and ANN5 [ 36 ]; and 17 TF encoding genes such as TGA4 [ 37 ], WRKY23 [ 38 ], and HB-7 [ 25 ] (Additional file 2 : Table S8). Overall, we identified a series of genes both related to 3D chromatin structure and induced by drought stress, which are closely related to cotton response to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…Cotton can alleviate osmotic stress under drought by mechanisms such as accumulating and transporting inorganic ions and small molecule organic substances. As one of the most important stress response hormones, the analysis of abscisic acid (ABA) is involved in many studies aimed at improving cotton water use efficiency and drought resistance [10]. Additionally, several TFs related to drought stress signal transduction have been identified in cotton, such as GhWRKY41, GhWRKY59, and GhMYB108-like [11][12][13].…”
mentioning
confidence: 99%
“…AHG3 interacts with PYL12 in response to ABA and functions specifically in seed germination and early seedling growth [ 48 ]. The Cotton GhPYLs are effective against the phosphatase activity of GhHAI2, GhAHG3, and GhABI2 [ 49 ]. We also found that CePP2C19 interacts with CePYR1, a member of the ABA receptor family, and provided further evidence that CePP2C19 is pivotal to ABA signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data led to the conclusion that low CePP2C19 expression reduces the plant’s ability to withstand drought. Reducing the expression levels of GhHAI2, GhAHG3, and GhABI2 in cotton has been shown to increase the plant tolerance to osmotic stress [ 49 ]. Group A PP2Cs inhibit the ABA signaling pathway by dephosphorylating SnRK2 type kinases, which leads to the degradation of these proteins [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Y2H method has been used for identification of unknown protein interactions in different crop plants, e.g., rice and wheat (Niu et al, 2016;Wang et al, 2016;Wang X. et al, 2018). This method is an effectual approach to identify the protein in genetic system of living cells and to study the interaction between proteins (Fields and Song, 1989;Shazadee et al, 2022). This Y2H technique cannot only measure the interaction between known proteins but also reveals the unknown proteins interaction with known proteins by screening the suitable yeast libraries.…”
Section: Introductionmentioning
confidence: 99%